The work of Magdalena Dobromila Rettigová as an example of Czech revival activity in the 19th century - Miller, Patrycja (Mundus Slavicus I, 2025)
The article presents the figure of Magdalena Dobromila Rettigová (1775–1845) – the first Czech female writer. The text presents her pedagogical and literary activities as well as her participation in the Czech National Revival. The early years of the writer’s life, which contributed to her activity in later years, are also described. Out of her literary output, Rettigová’s most important work was undoubtedly the home cookbook, which made her famous and because of which she is remembered as the creator of the Czech culinary nomenclature.